Viral loads in throat and anal swabs in children infected with SARS-CoV-2 - Chunhui Yuan; Hongmin Zhu; Yuan Yang; Xiaonan Cai; Feiyan Xiang; Huan Wu; Cong Yao; Yun Xiang; Han Xiao (Emerging Microbes and Infections)
Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) assay on anal swabs was recently reported to be persistently positive even after throat testing was negative during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. However, data about the consistent performance of RT-PCR assay on throat and anal swabs remain limited in paediatric patients. Here, we retrospectively reviewed RT-PCR-testing results of 212 paediatric patients with suspected SARS-CoV-2 infection at Wuhan Children’s Hospital. The diagnostic potential of these two types of specimens showed significant difference (positive rate: 78.2% on throat swabs vs. 52.6% on anal swabs, McNemar Test P = 0.0091) and exhibited a weak positive consistency (Kappa value was 0.311, P < 0.0001) in paediatric patients. Furthermore, viral loads detected on both throat and anal swabs also showed no significant difference (P = 0.9511) and correlation (Pearson r = 0.0434, P = 0.8406), and exhibited an inconsistent kinetic change through the course of SARS-CoV-2 infection. Besides, viral loads in the throat and anal swabs were correlated with different types of immune states, immune-reactive phase, and the resolution phase/immunologic tolerance, respectively. These findings revealed that RT-PCR-testing on throat and anal swabs showed significant difference for monitoring SARS-CoV-2 infection and correlated with different immune state in paediatric patients.